Nanocrystalline and stacking-disordered β-cristobalite AlPO4 chemically stabilized at room temperature: synthesis, physical characterization, and X-ray powder diffraction data. (7th June 2017) - Peplinski, B.; Adamczyk, B.; Formanek, P.; Meyer, C.; Krüger, O.; Scharf, H.; Reinsch, S.; Ostermann, M.; Nofz, M.; Jäger, C.; Adam, C.; Emmerling, F.
Abstract : This paper reports the first successful synthesis and the structural characterization of nanocrystalline and stacking-disordered β -cristobalite AlPO4 that is chemically stabilized down to room temperature and free of crystalline impurity phases. Several batches of the title compound were synthesized and thoroughly characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy, selected area electron diffraction, energy dispersive X-ray spectroscopy mapping in SEM, solid-state 31 P nuclear magnetic resonance ( 31 P-NMR) spectroscopy including the TRAPDOR method, differential thermal analysis (DTA), gas-sorption methods, optical emission spectroscopy, X-ray fluorescence spectroscopy, and ion chromatography. Parameters that are critical for the synthesis were identified and optimized. The synthesis procedure yields reproducible results and is well documented. A high-quality XRD pattern of the title compound is presented, which was collected with monochromatic copper radiation at room temperature in a wide 2 θ range of 5°–100°.